Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was just doing revision for an upcoming exam and I came across a question I do not know how to answer. It seems pretty simple, however I am having a blank moment. If anyone knows how to solve that I would really appreciate the help.

The question:

It is given that y = $\sin^{-1}(ax)$, where a is a positive constant and $-\frac{1}{a}\leq x\leq \frac{1}{x}$.

  • a) Find $\frac{dy}{dx}$ in terms of y and a.
  • b) Hence find $\frac{dy}{dx}$ in terms of x and a.
  • c) Hence, or otherwise, find $\int \frac{1}{\sqrt{1-9x^{2}}}dx$.
  • d) Find the exact value of $\int_{0}^{1/6}\sqrt{1-9x^{2}} dx$

I have finished parts a to c (workings below) but cannot seem to solve part d (I do realize it's probably relatively simple, however I have just spent good 45 minutes trying to solve it or find the answer and I can't seem to solve it)

$$ y=\sin^{-1}(ax)\\\sin(y)=ax\\\frac{dy}{dx}\cos(y)=a\\\Rightarrow\frac{dy}{dx}=\frac{a}{\cos(y)}=\frac{a}{\sqrt{1-\sin^{2}(y)}}=\frac{a}{\sqrt{1-a^{2}x^{2}}}\\\int\frac{1}{\sqrt{1-9x^{2}}}dx = \frac{1}{3}\int{\frac{3}{\sqrt{1-9x^{2}}}}dx=\frac{1}{3}\sin^{-1}(3x)+c$$

Any help would be greatly appreciated.

share|cite|improve this question
up vote 1 down vote accepted

For the last part, let $x = \dfrac{\sin(\theta)}{3}$. As $x$ goes from $0$ to $1/6$, we have that $\theta$ goes from $0$ to $\pi/6$. Also, $dx = \dfrac{\cos(\theta)}{3} d \theta$. Hence, $$I = \int_0^{1/6} \sqrt{1-9x^2} dx = \int_0^{\pi/6} \sqrt{1 - \sin^2(\theta)} \dfrac{\cos(\theta)}{3} d \theta = \int_0^{\pi/6} \dfrac{\cos^2(\theta)}{3} d \theta$$ Hence, $$I = \dfrac16 \int_0^{\pi/6} 2 \cos^2(\theta) d \theta = \dfrac16 \int_0^{\pi/6} (1 + \cos(2 \theta)) d \theta = \dfrac16 \left( \theta + \dfrac{\sin(2 \theta)}{2} \right)_{0}^{\pi/6}$$ Hence, $$I = \dfrac16 \left(\dfrac{\pi}{6} + \dfrac{\sin(\pi/3)}{2}\right) = \dfrac16 \left(\dfrac{\pi}{6} + \dfrac{\sqrt{3}}{4}\right) = \dfrac1{72} \left(2 \pi + 3 \sqrt{3} \right)$$

share|cite|improve this answer
Thanks a lot! :) This makes perfect sense, I can't believe I haven't spotted this way in all the time I spent trying to solve this problem. Lack of sleep is getting to me. Thanks again, you're a life savior! :) – Bart Platak Jun 6 '12 at 2:00

use this formula $$\int \sqrt{a^2-x^2}dx=\frac{1}{2}x\sqrt{a^2-x^2}+\frac{a^2}{2}\arcsin \frac{x}{a}+C$$ $$\int_{0}^{1/6}\sqrt{1-9x^{2}} dx$$ $$\left(\frac{3x}{6}\sqrt{1-9x^{2}}+\frac{1}{6}\arcsin\frac{3x}{1} \right)_{0}^{1/6}$$ $$\left(\frac{x}{2}\sqrt{1-9x^{2}}+\frac{1}{6}\arcsin\frac{3x}{1} \right)_{0}^{1/6}$$ $$(\frac{1}{12}\sqrt{1-\frac{9}{36}}+\frac{1}{6}\arcsin\frac{1}{2})-0$$ $$\frac{\sqrt{27}}{72}+\frac{\pi}{36}$$ $$\dfrac1{72} \left(2 \pi + 3 \sqrt{3} \right)$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.